Availability of agricultural products in the Farmers’ Market in San Ramón, Alajuela, Costa Rica - Sánchez-Brenes, Ronald (2019)
Costa Rican Farmers’ Markets are agricultural product distribution and supply centers, which can contribute to the food and nutritional security of the country. The present study is aimed at measuring the diversity, seasonality, and frequency of agricultural products in the San Ramón Farmers’ Market (FASR) to ensure the Market’s physical availability of products to customers. A total of 165 agricultural products were registered in the sections, over a period of one year (November 2015-October 2016). From all agricultural products observed, 35% correspond to fruits, 21% to vegetables, 21% to medicinal and aromatic plants, 9% starchy roots and other foods with high carbohydrate content, 7% to animal products, 4% to legumes, and 3% to other products.